Determination of the parameters of Modified Cam-Clay model for paddy grain. (July 2017) - Du, Xiaocui; Cheng, Xuduo; Gao, Mengyao
Abstract: To determine the parameters of Modified Cam-Clay model for paddy grain, a constitutive stress-strain equation, was used to study the stress-strain behavior of paddy grain. Triaxial tests were carried out four different moisture contents of paddy. This elastoplastic model contains five parameters: the critical state ratio M, the logarithmic hardening modulus λ, the isotropic swelling index κ, the elastic modulus E and the Poisson's ratio ν, which can be evaluated in axial compression test and the isotropic compression test. The experimental results reveal that the M of paddy grain (Xiandao 118) with four different moisture contents (11.75%, 13.34%, 14.93% and 16.43%w.b.) were 2.1195, 2.1093, 2.0931 and 2.0110, the λ were 0.1408, 0.1390, 0.1355 and 0.1304, the κ were 0.1018, 0.0935, 0.0986 and 0.0948, and the ν were 0.145, 0.152, 0.155 and 0.166, respectively. The relation equations between the elastic modulus E with generalized shearing force q and mean principal stress p were obtained from the analysis of the experimental results. The comparisons between the Modified Cam-Clay model calculated values and measured values showed that the calculated parameters of the Modified Cam-Clay model are reasonable and the model can adequately describe the stress-strain behavior of paddy grain for the conditions tested. Highlights: The parameters of the Modified Cam-Clay model of paddy grain were calculated. The moisture content has little effect on the model parameters of paddy grain. The relation equations between the elastic modulus E with q and p were obtained. The model can adequately describe the stress-strain behavior of paddy grain.